Advancing multifunctional landscapes: CGIAR MFL Community of Practice charts next steps for collaboration and impact - Ojanji,Wandera (CGIAR System Organization, 2025)
The CGIAR Multifunctional Landscapes (MFL) Community of Practice (CoP) serves as a collaborative platform for advancing integrated landscape approaches that balance agricultural productivity, biodiversity conservation, and livelihood outcomes. This blog documents the outcomes of a recent MFL CoP convening, where researchers and practitioners reflected on emerging priorities, shared experiences across regions, and identified practical pathways for strengthening collaboration. Discussions highlighted the value of cross-program learning, coordinated knowledge exchange, and alignment between research, policy engagement, and on-the-ground implementation. The session underscored the importance of sustaining the CoP as a mechanism for connecting diverse expertise, supporting adaptive management, and translating scientific evidence into actionable insights. Looking ahead, the CoP identified concrete next steps to deepen engagement, enhance knowledge products, and support the CGIAR MFL programme’s contribution to inclusive, resilient, and multifunctional landscape management.